Implementasi Sistem Odoo Proses Planning Menu dan Reporting Menggunakan Metode RAD Pada UMKM Dapurbeta - Bagir, Syeikh; Budiyono, Avon (LPPM STIKOM Tunas Bangsa, 2024)
Currently, many small and medium enterprises (SMEs) in the food and beverage sector are growing; however, most face challenges in sustaining their businesses, particularly due to competition, poor management, and a lack of technological knowledge. Digitalization has become a crucial solution to address these issues, especially in data collection and analysis that support business decision-making. Dapurbeta, a restaurant offering traditional Indonesian dishes that frequently change monthly, faces challenges in menu planning and reporting processes due to the lack of an integrated system. To address these issues, Dapurbeta implemented an Enterprise Resource Planning (ERP) system using the Odoo application and the Rapid Application Development (RAD) method. The outcomes of this research include the design of business processes tailored to Dapurbeta’s needs, as well as the implementation of a menu planning module and dashboard configured in Odoo. This system is expected to improve the company's operations and facilitate decision-making, enabling Dapurbeta to remain sustainable and competitive in the long term.